Деякі питання вдосконалення діяльності органів та підрозділів Національної поліції України - Бугайчук, К. Л.; Bugaychuk, K. L.; ResearcherID: I-5612-2016; Костянтин Бугайчук (Право і безпека. – 2019. – № 2 (73). – С. 13-19, 2019)
Досліджено основні недоліки нормативного забезпечення й організації діяльності Національної поліції України за окремими напрямами. На підставі аналізу чинного законодавства України, підзаконних нормативних актів та наказів МВС України й Національної поліції України сформульовано пропозиції, спрямовані на врегулювання правового статусу Національної поліції, ухвалення базових положень про її окремі види; вдосконалення процесу планування в системі Національної поліції, застосування в її діяльності сучасних методів стратегічного аналізу та цілепокладання; оптимізацію правового й організаційного забезпечення діяльності поліцейських комісій. Отримані результати є складовою частиною наукового дослідження автора щодо організації та здійснення публічного адміністрування в органах Національної поліції України й можуть бути використані для здійснення інших фундаментальних і прикладних наукових досліджень у сфері управлінської діяльності правоохоронних органів.

The author has studied the main shortcomings of regulatory provision and organization of the activity of the National Police of Ukraine according to certain areas. On the basis of the analysis of the current legislation of Ukraine, by-laws and orders of the Ministry of Internal Affairs of Ukraine and the National Police of Ukraine, the author has formulated propositions aimed at regulating the legal status of the National Police, adoption of basic provisions on its certain types; improvement of the planning procedure within the National Police system, application of modern methods of strategic analysis and goal-setting in its activity; optimization of legal and organizational provision of the activities of police commissions. In particular, the author has offered to include the National Police of Ukraine as the central executive authority in the content of the basic law “On Central Executive Agencies”, to adopt provisions on certain types of police, to improve the content of the departmental order of the National Police on the organization of planning, and to develop appropriate methodological recommendations for police officers on this issue, to harmonize the content of regulatory documents on the activities of police commissions on setting the priorities of police activity and highlighting the results of their work on the official website of the National Police. The obtained results are an integral part of the author’s scientific research into the organization and implementation of public administration within the agencies of the National Police of Ukraine and can be used to carry out other fundamental and applied scientific studies in the field of law enforcement agencies.

Исследованы основные недостатки нормативного обеспечения и организации деятельности Национальной полиции Украины по отдельным направлениям. На основе анализа действующего законодательства Украины, подзаконных нормативных актов и приказов МВД Украины и Национальной полиции Украины сформулированы предложения, направленные на урегулирование правового статуса Национальной полиции, принятие базовых положений о её отдельных видах; усовершенствование процесса планирования в системе Национальной полиции, применение в её деятельности современных методов стратегического анализа и целеполагания; оптимизацию правового и организационного обеспечения деятельности полицейских комиссий. Полученные результаты являются составляющей частью научного исследования автора вопросов организации и осуществления публичного администрирования в органах Национальной полиции Украины и могут быть использованы для проведения других фундаментальных и прикладных научных исследований в сфере управленческой деятельности правоохранительных органов.
Some issues on improving the activity of the agencies and units of the National police of Ukraine
Некоторые вопросы совершенствования деятельности органов и подразделений Национальной полиции Украины
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; Национальная полиция Украины; National police of Ukraine; поліція; police; полиция; публічне адміністрування; кадрове забезпечення; поліцейські комісії; public administration; staffing; police commissions; публичное администрирование; кадровое обеспечение; полицейские комиссии